Pastoral Communities Based on a Model of Self-Help Groups as a Response of the Church to the Contemporary Social Changes - Grzegorz Wąchol (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2020)
Dynamic changes in modern society generate new situations in the lives of believers, which require pastoral care. The Church should respond to the spiritual needs of all those in need, but with the decreasing number of ordained priests in Europe, organizational capacity in this part of the world is becoming increasingly limited. This article is an attempt to respond to the above problems and, using the example of the Catholic Church in Poland, shows the possibility of instilling a model of self-help groups for specialist pastoral care involving people experiencing life crises and wanting more intense religious development.